seL4 in Australia: From Research to Real-World Trustworthy Systems. - HEISER, GERNOT; KLEIN, GERWIN; ANDRONICK, JUNE (Communications of the ACM, 2020)
The article discusses the development and function of the computer software seL4 microkernal in Australia, and describes computer security and computer architecture, the evolution of the kernal, and the establishment of an sel4 Foundation.